PLAG1 fusions define a third subtype of CNS embryonal tumor with PLAG family gene alteration - Keck, Michaela-Kristina; Al-Hussaini, Maysa; Amayiri, Nisreen; Yiadom, Akosua Adoma Boakye; Chamyan, Gabriel; Cheesman, Edmund; Faure-Conter, Cécile; Garcia-Ariza, Miguel; Gauchotte, Guillaume; Hasselblatt, Martin; Jorgensen, Mette; Kilday, John-Paul; et al. (Acta neuropathologica, 2025)
CNS embryonal tumors with PLAGL amplification (ET, PLAGL) are a recently described tumor type marked by amplification of one of the PLAG family genes, PLAGL1 or PLAGL2. Separately, a supratentorial, ependymoma-like CNS tumor type with PLAG family alteration, namely PLAGL1 fusion, was also reported (NET_PLAGL1). Here, we use DNA methylation profiling in combination with copy number, RNA-seq, and histological analysis to characterize and classify a novel group of CNS embryonal tumors harboring PLAG1 gene fusions (n=12). Through our screening, we identified a subset of CNS tumors (n=12) epigenetically distinct from other known CNS tumor types, but clustering close to the PLAGL1- and PLAGL2-amplified ET, PLAGL subtypes in our t-SNE analysis. Copy number profiles indicated putative PLAG1 fusions, which were confirmed in 9/12 tumors (not determined in 3/12). Different 5’ fusion partners (ASAP1, ADGRG1, TMEM68, TCF4, CHD7, NCALD, HNRNPK, LOC105378102) were identified that upregulate wild-type PLAG1 through promoter hijacking. Expression analysis shows upregulation of PLAG1 as well as IGF2, DLK1, Desmin, CYP2W1, and RET, which are also robustly expressed in PLAGL1/2-amplified tumors. Patient characteristics, survival data, and clinical/imaging analysis show additional similarities to PLAGL1/2-amplified tumors. Median age at diagnosis was 5 years, tumors were located throughout the neuroaxis, and original histological diagnoses were heterogeneous. The tumors demonstrated morphologic heterogeneity, with most composed of densely cellular areas of primitive small blue cells, alongside focal regions showing clear cell morphology, microcystic changes, and ependymoma-like perivascular pseudorosettes. Applied treatment regimens were also heterogeneous, but some favorable responses to therapy were observed. In summary, we describe a third subtype of PLAG family-altered pediatric CNS embryonal tumor characterized by PLAG1 gene fusion, which leads to upregulation of PLAG1 and downstream genes. We therefore propose to rename ET, PLAGL to ET, PLAG (CNS embryonal tumor with PLAG family gene alteration) together with a specification of the respective subtype.
Gesehen am 12.01.2026